International Conference of Young Scientists "Advances in Botany and Ecology" (dedicated to the 120th anniversary of D.K. Zerov,Poltava, 15–20 September 2015) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
International Conference of Young Scientists "Advances in Botany and Ecology" (dedicated to the 120th anniversary of  D.K.Zerov, Poltava, 15–20September 2015)